Tributação e desenvolvimento local: um estudo do exercício da competência tributária no município de Palmeira dos Índios - AL - Silva, Paula Laíse de Vasconcelos Ribeiro (2019)
The present work has as objetive to study the tax jurisdiction in the municipality of Palmeira dos Indios / Alagoas, a city in which Graciliano Ramos was mayor between the years of 1928 and 1930. The study is pertinent to the difficulty which the Brazilian municipalities have faced in order to institute and effectively collect the taxes of their competence, even though the Federal Constitution of 1988 granted them political, administrative and legislative autonomy in the sphere of predominance of local interest. The financial autonomy of the Municipalities is an essential condition for the performance of its other activities, and the tax question is a point where the most relevant aspects of municipality management are covered. However, municipality tax jurisdiction is not always exercised, or irresponsibly, especially in smaller municipalities. Those most affected by this situation are taxpayers and citizens in general, since they have their fundamental rights constantly violated by excesses and omissions of a deficient and ineffective tax policy. Thus, it is necessary to analyze how the exercise of municipality taxation influences local development. The elaboration of an efficient tax policy should not be confused with an increase in the tax burden, but be based on an exercise of the Power of Tax that attentive to local peculiarities, attracting and making feasible the development of economic activities and citizen participation in the process, always observing the principles of transparency, tax justice, legal certainty and safeguarding fundamental rights as a whole.